Statistical aspects of the design and analysis of clinical trials - Everitt, Brian (Imperial College Press ; Distributed by World Scientific Pub. Co., 2004)
Fully updated, this revised edition describes the statistical aspects of both the design and analysis of trials, with particular emphasis on the more recent methods of analysis. About 8000 clinical trials are undertaken annually in all areas of medicine, from the treatment of acne to the prevention of cancer.